Transient elastography in healthy subjects and factors influencing liver stiffness in non-alcoholic fatty liver disease: An Italian community-based population study - Conti, Fabio; Vukotic, Ranka; Foschi, Francesco Giuseppe; Domenicali, Marco; Giacomoni, Pierluigi; Savini, Sara; Lanzi, Arianna; Dall’Aglio, Anna Chiara; Saini, Gaia; Matroroberto, Marianna; Bernardi, Mauro; Stefanini, Giuseppe Francesco; et al. (Digestive and liver disease, 2016)
Few studies have been performed to explore parameters that influence liver stiffness measurement (LSM) using transient elastography in general population. To explore factors influencing LSM in healthy and in subjects with non-alcoholic fatty liver disease (NAFLD). LSM was performed in a well-characterized cohort of subjects aged between 30 and 63 years. After exclusion of any causes of liver disease, the healthy cohort was defined and was compared with participants with NAFLD. The 95th percentile value of LSM in healthy was used as a cutoff suggesting relevant fibrosis. Among 780 subjects evaluated, 331 were defined as healthy. The median value was 4.4kPa (3.7–5.2) and the 95th percentile was 6.8kPa. LSM was not influenced by gender, age, anthropometrics and biochemical parameters. Only insulin resistance was independently associated with increasing of LSM. In the cohort of 157 subjects with NAFLD, LSM was higher than in healthy (5.6±1.9 vs 4.6±1.3kPa; p<0.001). On multivariate analysis, the degree of steatosis was independently associated with increasing of LSM in NAFLD cohort (β=0.271; 95% CI=0.026–0.095; p<0.001). Participants with diabetes and/or severe steatosis had the highest probabilities of relevant fibrosis. LSM varies between 3.7 and 5.2kPa in healthy Caucasians and is influenced only by insulin resistance. In NAFLD, severe steatosis and diabetes are factors influencing LSM.